Anti-Tyro3 IgG Associates with Disease Activity and Reduces Efferocytosis of Macrophages in New-Onset Systemic Lupus Erythematosus. (11th November 2020) - Zhou, Zhuochao; Xu, Aining; Teng, Jialin; Wang, Fan; Tan, Yun; Liu, Honglei; Cheng, Xiaobing; Su, Yutong; Shi, Hui; Hu, Qiongyi; Chi, Huihui; Li, Jian; et al.
Abstract : Background . Systemic lupus erythematosus (SLE) is a disease characterized by the production of a large number of autoantibodies. Defected phagocytosis of macrophage plays an important role in innate immunity in the pathogenesis of SLE. Tyro3 is a receptor responsible for the recognition of apoptotic cells during efferocytosis by macrophages. To investigate the role of Tyro3 receptor in macrophages' efferocytosis of apoptotic cells in SLE, we aimed to reveal the clinical relevance and impact of Tyro3 autoantibody on SLE. Methods . The serum levels of IgG-type autoantibody against Tyro3 receptor were detected in new-onset, treatment-naïve SLE patients (n = 70 ), rheumatoid arthritis (RA) (n = 24 ), primary Sjögren's Syndrome (pSS) (n = 21 ), and healthy controls (HCs) (n = 70 ) using enzyme-linked immunosorbent assay (ELISA). The effects of purified Tyro3 autoantibody from SLE patients on the efferocytosis of human monocyte-derived macrophages were measured by flow cytometry and immunofluorescence. Results . The serum levels of IgG-type autoantibody against Tyro3 receptor were significantly elevated in patients with SLE compared to RA, pSS, and HCs (all p < 0.0001 ). The levels of anti-Tyro3 IgG were positively associated with the SLE disease activity index (SLEDAI) score (r = 0.254, p = 0.034 ), erythrocyte sedimentation rate (ESR) (r = 0.430, p < 0.001 ), C-reactive protein (CRP) (r = 0.246, p = 0.049 ), and immunoglobulin G (IgG) (r = 0.408, p = 0.001 ) and negatively associated with haemoglobin (Hb) (r = − 0.294, p = 0.014 ). ROC curves illustrated that the anti-Tyro3 antibody could differentiate patients with SLE from HCs. Furthermore, flow cytometry and immunofluorescence demonstrated that purified anti-Tyro3 IgG inhibited the efferocytosis of macrophages (p = 0.004 and 0.044, respectively) compared with unconjugated human IgG. Conclusions . These observations indicated that autoantibody against Tyro3 was associated with disease activity and could impair efferocytosis of macrophages. It might be a potential novel disease biomarker and might be involved in the pathogenesis of SLE.